Beneficial effects of Aloe vera in treatment of diabetes: Comparative in vivo and in vitro studies - Amira Mourad Hussein Abo-Youssef; Basim Anwar Shehata Messiha (Faculty of Pharmacy, Cairo University, 2013)
In the present investigation, the antidiabetic effect of Aloe vera leaf pulp extract was studied in vivo and in vitro as compared to glimiperide. Diabetes was induced experimentally in adult male albino rats by single-dose intraperitoneal injection of streptozotocin (50 mg/kg body weight). The in vitro study was performed using isolated islets of pancreas from adult female albino rats. Both aloe extract (10 ml/kg, p.o.) and glimiperide (10 mg/kg, p.o.) significantly decreased serum glucose and significantly increased serum insulin levels as compared to control diabetic rats. Serum levels of malondialdehyde (MDA) and superoxide dismutase (SOD) were significantly decreased while blood glutathione (GSH) was significantly increased by aloe treatment as compared to diabetic rats. Effect of aloe was better than the effect of glimiperide. Regarding the in vitro study, both aloe (10 μl/l) and glimiperide (10 μmol/l) significantly increased both basal and stimulated insulin secretion from the isolated islets of pancreas as compared to control. These results show a promising antidiabetic effect of aloe for further clinical trials regarding clinical use of aloe extract for treating type II diabetes.